Pengaruh Gross Profit Margin Dan Net Profit Margin Terhadap Pertumbuhan Laba PT Indofood Sukses Makmur Tbk - Jamaluddin, Andi; Sari, Yulistira (Jurnal Online Manajemen ELPEI, 2026)
This study aims to analyze the effect of Gross Profit Margin (GPM) and Net Profit Margin (NPM) on profit growth at PT Indofood Sukses Makmur Tbk for the 2020– 2024 period. This research employs a quantitative descriptive approach with acausal associativedesign, using secondarydataobtainedfromthecompany’sannual financial statements published by the Indonesia Stock Exchange. Data analysis was performed using multiple linear regression through the SPSS software to examine both partial and simultaneous effects between variables. The results indicate that GPM has a positive and significant effect on profit growth, while NPM has a positive but not significant effect. Simultaneously, bothvariablesshowa positive yet insignificant effect on profit growth. The coefficient of determination (R²) of 0.686 suggests that 68.6% of the variation in profit growth can be explained by GPM and NPM, with the remaining 31.4%influenced by otherfactorsoutside the model. These findings imply that the efficiency of cost management at the gross profit level plays a more dominant role in increasing profit growth compared to net profit efficiency.